TEACHING AND PSYCHO - PEDAGOGICAL PRIORITIES IN THE REGULATION OF THE HANDBALL GAME FOR THE CATEGORY OF CHILDREN AND PLAYERS OF MINIHANDBALL - LEUCIUC Florin-Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Reducing the age scale when it comes to selection and the practice of the minihandball by children requires teaching and psychopedagogical completions concerning the regulation of the handball game. The teaching and psycho - pedagogical aspects must be taken into account when we talk about the minihandball players (players who are between 7 and 10 years old) and children between 11 and 14 years old. The training of young sportsmen must be carried out in accordance with the particularities of the age, and when it comes to the match we should take into account the technical and psycho-pedagogical aspects presented in this article.